(untitled) (Comparative & International Education Series, 2021)
Nonnative English speakers who teach at English-medium institutions in North America have frequently been the subject of student complaints. From the perspective of many undergraduate students who are native speakers of English, these instructors lack the linguistic competence to serve as instructors. This chapter synthesizes the existing literature on the complaints and resistance East Asian women international faculty members (EAWIF) receive from undergraduate students with a particular focus on how such complaints and resistance were related to their nonnative English. The findings reveal that the students viewed Asian accent as incomprehensible, unclear, and hindering their learning. In return, EAWIF made unilateral efforts to overcome their weaknesses in English and adapt to the teaching and interactional styles with which the students were familiar. The chapter discusses the findings in the context of internationalization of higher education.